Children's participation in custody and access proceedings - Che Soh @ Yusoff, Roslina (International Islamic University Malaysia, 2014)
The right of children to express their views in all matters affecting their lives is regarded as one of the important factors that concern their welfare. The United Nations Convention on the Rights of the Child and social science research support children's right to participate in family law proceedings, particularly in decisions of custody disputes, though there is no clear consensus on how this should be done. Many jurisdictions such as Australia and England incorporate several measures in their legislations in ensuring the meaningful involvement of children in family dispute resolution processes. The laws in Malaysia similarly uphold this right but do not provide specific measures to obtain the views of children. This paper seeks to discuss the importance of the child’s participation in the context of custody disputes and to examine the measures in which the views of children can be obtained. In doing so, it attempts to provide an overview of the current laws and the approach of the Civil and the Shariah courts in Malaysia in considering the views of children in custody disputes. For purposes of comparison, it briefly examines the legislations and the court practices in Australia and England on this matter. The purpose is to determine the best measure to be adopted by Malaysia and to propose statutory and non-statutory changes to ensure that children in Malaysia are given the right to have their voices heard in family law proceedings.